Sports charity and gendered labour - Palmer, Catherine (Emerald Publishing Limited, 2021)
In cities around the world, in parks and roadways, people are taking part in sporting charity challenges. Corporate sponsorship has transformed these events into philanthropic endeavours that bring corporate marketing strategies together with medical research and social care agendas. Despite this growth in popularity, little academic attention has paid attention to the ways in which gendered labour shapes the nature of sports-charity events. Sports Charity and Gendered Labour explores a series of questions about the meaning and politics of physical activity, and notions of gender, labour and responsibility.Drawing upon auto-ethnography, studies of major events, in-depth interviews, and analysis of social media, Sports Charity and Gendered Labour provides examples for teaching and knowledge sharing across analyses of gender, sport, leisure, health and wellbeing in ways that will have broad relevance to a range of audiences.
Keywords: Charity sports events.; Sex role.; Sports -- Sociological aspects.; Sports & Recreation -- Cultural & Social Aspects.; Sporting events & management.; elektronické knihy; electronic books